Successful Treatment With Intrathecal and Intravenous Polymyxin B-Based Combination Against MDR Acinetobacter baumannii Meningitis in Pediatric Patient: A Case Report - Xing, Haiyan; Cheng, Caiyi; Zhang, Yihua; Cai, Yongqing; Wang, Xianfeng; Deng, Dongmei; Xu, Lunshan; Xu, Minhui; Chen, Jianhong (Frontiers in Pediatrics, 2021)
Background Nosocomial meningitis with multidrug-resistant (MDR) or extensively drug resistant (XDR) Acinetobacter baumannii is one of the life-threatening complications in neurosurgery. Treatment of these infections is challenging, because of poor diffusion of the available antibiotics into cerebrospinal fluid (CSF). Intrathecal (ITH) or intraventricular (IVT) administration of antibiotics is increasingly used as the last treatment option against MDR/XDR Gram-negative bacteria meningitis that is not responding to intravenous (IV) regimens, yet pertinent data in pediatric patients is scarce. Case presentation A 14-year-old male patient developed meningitis from a MDR strain of Acinetobacter baumannii following endoscopic endonasal resection of craniopharyngioma. Despite a combination therapy involving IV tigecycline, we observed clinical and bacteriologic failure. The patient was then successfully treated with ITH and IV Polymyxin B-based combination. Quantification of tigecycline and polymyxin B in CSF was performed with two-dimensional high-performance liquid chromatography (2D-HPLC) and high performance liquid chromatography coupled with tandem mass spectrometry (HPLC-MS/MS), respectively. Adverse drug reactions (neurotoxicity and skin hyperpigmentation) probably induced by polymyxin B were acceptable and reversible. Conclusions The case illustrates ITH and IV Polymyxin B-based combination is an optimal therapeutic option against MDR Acinetobacter baumannii meningitis in this pediatric patient. In the future, real-time PK/PD information obtained from patients during ITH/IVT polymyxin B therapy is urgently required for dose optimization.